Peran Warga Pantura pada Sektor Perikanan Tangkap di Pelabuhan Perikanan Samudera Cilacap (PPSC), Kabupaten Cilacap - Darwanto, Agus; Chasanah, Fazri Uswatun; Wulandari, Silvi Fatika (Nekton, 2023)
Many farmers and fishermen from the north coast of Java Island (Pantura) migrated to the south coast of Java to try their luck as fishermen in the Cilacap Ocean Fisheries Port (PPSC). The urbanization of Pantura residents to Cilacap has been ongoing for more than 50 years. This study aims to determine the contribution of Pantura residents to the capture fisheries sector in the PPSC. Data were collected through observation, interviews, surveys, and documentation. Data analysis used descriptive analysis with reduction and interpretation as well as ANOVA and simple linear regression analysis. Based on the survey results, 90% of respondents stated that the reason for Pantura residents to migrate to Cilacap was to increase their income. According to 93.3% of respondents, their arrival at PPSC contributed to the capture fisheries sector in the Cilacap Regency. The results of the ANOVA test show a significance of <0.05, which means that there is an influence from the arrival of Pantura residents in increasing capture fishery production in PPSC. The correlation between the arrival of Pantura residents in PPSC and the increase in capture fishery productivity was 43.5%, with an influence level of 18.9%. Thus, the role of Pantura residents is very important in increasing capture fishery production in Cilacap.